Pembelajaran Matematika yang Mengacu Multiple Inteligences pada Materi Statistik di Kelas Xi Ips Sma Negeri 2 Batu - Dedy Setyawan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
The number of national examination become decrease, one of the subjects is mathematic. Thus, it needs to apply a learning based on student intelligences. It can be applied in mathematic base on student personal intelligence. The research used learning with multiple intelligences in mathematic subject. It was applied at Statistic lesson to eleventh grade students of SMAN 02 BATU. The aim of the research is to find out how were the activities and the result of study. The research design used in this study was a descriptive qualitative research. The subject of research was the students of XI IPS class on SMAN 02 BATU. The variable of this research were student’s activities and students score. The instruments used of this study were questionnaire and students score. Data analysis used of this study was percentage analyzing to measure the activities and students score. The result of the research showed that the number of students activities was quite enough with 68, 63%. The result of completeness analyzing student learning after using multiple intelligence with 28 students was complete and one of them was failed. The completeness of personal classical study with SKBM was 96, 55%.